EPIDEMIOLOGY OF PARACOCCIDIOIDOMYCOSIS - MARTINEZ, Roberto (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
The epidemiological characteristics of paracoccidioidomycosis were reviewed and updated. The new endemic areas in Brazil were discussed in the section regarding the geographic distribution of the mycosis. Subclinical infection with Paracoccidioides brasiliensis was discussed on the basis of skin test surveys with antigens of the fungus, seroepidemiological studies, and disease cases outside Latin America. Large case series permitted a comparison of the prevalence of the mycosis in different regions, its estimated incidence and risk factors for the development of the disease. Aspects modulating the expression of the clinical forms of paracoccidioidomycosis are also presented. This review also deals with diseases associated with the mycosis, opportunistic paracoccidioidomycosis, lethality, mortality and infection and disease in animals.